Handbook of plant and crop stress - Pessarakli, Mohammad , 1948- (Books in soils, plants, and the environment, 2011)
"The dynamic and expanding knowledge of environmental stresses and their effects on plants and crops have resulted in the compilation of a large volume of information in the last ten years since the publication of the second edition of the Handbook of Plant and Crop Stress. With 90 percent new material and a new organization that reflects this increased knowledge base, this new edition, like the first two, provides comprehensive and complete coverage of the issues on stress imposed on plants and crops. Accessibility of knowledge is among the most critical of factors involved with plant/crop stress problems. Without due consideration of all the factors contributing to a specific plant/crop stress problem, it is unlikely that a permanent solution can be found. Facilitating the accessibility of the desired information, the volume is divided into ten sections. Each section consists of one or more chapters that discuss as many aspects of stress as possible. While many references cover soil salinity, sodicity, specific plant/crop salt and water stress, pollution, and other environmental stresses, they exist relatively in isolation, focusing mainly on one specific topic. Prepared with input from more than a hundred contributors from twenty seven countries, this book combines information on these interrelated areas into a single resource. Packed with illustrations, figures, and tables, covering plant/crop stress problems from the soil to the atmosphere, this book puts this expanded environmental stressors knowledge base within easy reach."--Publisher's description